Money, interest and economic activity in Ireland - Thom, DR (Economic & Social Studies, 1974)
Recent studies have provided evidence that economic activity in Ireland responds to changes in certain monetary aggregates.1 Thomas F. Hoare, for example, employs a 'Monetarist Model of Income Determination' to investigate the linkages between money, autonomous expenditure and aggregate income. Hoare's model relates nominal income (Y) to current and lagged values of a composite variable (Q) which is equated to the sum of exports, net external capital flows and changes in the banking system supply of domestic credit, the latter element of Q being equal to the money stock minus the banks net external assets.2 In the present paper, we investigate these macroeconomic relationships in a model similar to Hoare's but which gives explicit recognition to the openness o f the Irish economy and the consequent endogeneity of monetary aggregates.
Keywords: Economics; Ireland